Pseudopterygium After Limbal Dermoid Cyst Excision in a Child with Goldenhar Syndrome: Poster Presentation - Case Report - Ophthalmologist - CAESARITA, DEA PRITA; Barliana, Julie Dewi (Majalah Oftalmologi Indonesia, 2023)
Introduction : Goldenhar syndrome is a rare congenital disorder also known as oculoauricularvertebral dysplasia. Limbal dermoid associated with this syndrome. This case report aims to present an reccurent pseudopterygium after three times limbal dermoid cyst excision in patient with Goldenhar syndrome. Case Illustration : Patient 13 years old male with pseudopterygium in right eye. Visual acuity both eyes 6/6 snellen chart. Fibrovascular tissue from tarsal conjunctival inferotemporal to 2 mm limbal cornea in right eye. Patient had limbal dermoid cyst in right eye since birth and underwent limbal dermoid cyst excision for three times. First time surgery used amniotic membrane transplantation, then second and third surgery used conjunctival limbal graft. Goldenhar syndrome have been diagnosed since the age of 2 years old. External examination noticed asymmetrical hemifacial microsmia, grade III microtia right ear, conduction deafness, and laryngomalacia. Discussion : Limbal dermoid cyst is one of characteristic of Goldenhar syndrome. In this case pseudopterygium grade II in right eye developed after limbal dermoid cyst excision for three times. Limbal dermoid simple excision may lead to corneal vascularization persistent epithelial defect, scar, and pseudopterygium. Various surgical include superficial keratectomy, amniotic membrane transplantation and lamellar or penetrating keratoplasty. Pseudopterygium still occurs in this case, even though recurrence has been prevented by administration of amniotic membrane transplantation and conjunctival limbal graft. Conclusion : We should be concerned about management of limbal dermoid cyst with Goldenhar syndrome to prevent recurrent pseudopterygium.